The Early Beckett's Approach to Reality through a Textual Struggle with Rimbaud. Issue 2 (September 2017) - Fukaya, Kiminori
Abstract : In his early career, Beckett often mentioned an aesthetic of 'incoherent reality', which he felt was characteristic of Arthur Rimbaud. Critics have agreed that Rimbaud influenced on Beckett in the 'incoherent' use of language, while the importance of the idea of 'reality' has yet to be explored. In this article, I attempt to elucidate Beckett's view of incoherent reality and how he formulated it through Rimbaud. The early part of my analysis, drawing on Proust, differentiates young Beckett's perspective of reality from literary symbolism and explains why he found elements of reality in Proust and Rimbaud rather than Mallarmé and W.B. Yeats. Axel's Castle by Edmund Wilson, a classical study of literary symbolism, supports this differentiation; Wilson addresses Rimbaud's social and mercantile activity, which is barely seen in other reclusive symbolists. I speculate that Beckett may have read Wilson's book because descriptions about symbolism, which are quite similar to Wilson's, are present in the notes taken by Leslie Daiken as a student of Beckett's at Trinity College Dublin. Moreover, allusions to Rimbaud in works such as 'Enueg I' or Mercier et Camier show how Beckett focussed on the incoherent reality and was distanced from Rimbaud's mysterious side. On the basis of these arguments, the final part of the article examines the meaning of the 'reality of insane areas of silence' discussed in Beckett's first novel, Dream of Fair to Middling Women, to prove that he began to diverge from Rimbaud with an aesthetic of indolence, which would shape his own view of incoherent reality.